Pengaruh Struktur Kepemilikan Keluarga Terhadap Kinerja Perusahaan Pada Sektor Property, Real Estate dan Konstruksi Bangunan - Evelina Kurniawan; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
This study aimed to examine and to prove the influence of family ownership structure on company performance. The family ownership structure measured by using family members who sit managerial or have a 10% stock. Firm performance used in this research measured by using ROA. This research used control variables of GCG score and sales growth. The research was quantitative research and the data used were secondary data in the form of annual report. The sample used in this study was 185 observations in the sector of property, real estate and building construction companies listed in Indonesia Stock Exchange from 2010-2015. The data analysis method used was Software Statistic for Social Science (SPSS) version 24 to know the relationship between the two variables. The result of research showed that family ownership structure had positive affect to company performance, gcg score had positive affect to company performance, while sales growth had positive affect to company performance.